Discovery of CMNPD31124 as a novel marine-derived PKMYT1 inhibitor for pancreatic ductal adenocarcinoma therapy: computational and biological insights - Huang, Chaojie; Wang, Ting; Chen, Rui; Xu, Yunyun (Frontiers in Pharmacology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the deadliest cancers due to its late diagnosis, resistance to therapy, and a dismal 5-year survival rate of only 12%. Overexpression of PKMYT1—a key regulator of the cell cycle—correlates with poor patient outcomes, making it a promising therapeutic target. In this study, we identify CMNPD31124, a novel marine-derived indole alkaloid, as a potent PKMYT1 inhibitor. Molecular docking revealed that CMNPD31124 has superior binding affinity compared to the reference compound Cpd 4, forming robust interactions with critical residues such as CYS-190, TYR-121, and GLY-122. Molecular dynamics simulations further demonstrated its stable binding conformation and dynamic adaptability, with Chai-1 modeling supporting a covalent binding mechanism at the PKMYT1 active site. Importantly, in vitro assays showed that CMNPD31124 exhibits an IC50 of 18.6 μM in MiaPaCa-2 cells and 31.7 μM in BXPC3 cells, while concentrations up to 80 μM did not significantly affect normal pancreatic cells. Despite these promising results, toxicity predictions indicate potential hepatotoxicity and neurotoxicity, highlighting the need for further structural optimization. This work lays a solid foundation for the rational design of PKMYT1 inhibitors by integrating computational methods with insights from marine natural products.